HUBUNGAN PENGUASAAN KOSAKATA BIDANG JURNALISTIK DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS XII SMK NEGERI 2 BUKITTINGGI - Tressyalina, Rahma Dini Syahrul R., (Universitas Negeri Padang, 2017)
This research aims to describe relationships between vocabulary mastery of the field of journalistic with writing skills text news the students of class XII SMK Negeri 2 Bukittinggi. The type of this research is quantitative research using descriptive and the statistic correlation methods. Population and sample in this research is the student of the XII vocational high school, two, Bukittinggi. The population in this research is 42 students who are registered in academic year of 2017/2018. The results of research show that the mastery of the vocabulary of the field of journalism really help students in writing the text of the news. From the results of this research can be drawn the conclusion that there is a significant relationship (mean) between mastery of the vocabulary of the field of journalistic text writing skills with the news is significant on the degree of freedom, n-1, and it is significant at 95% of confident level since 10.32 of t-statistic value is greater than 1.68 of t-table value. Kata kunci: hubungan, penguasaan kosakata bidang jurnalistik, keterampilan menulis teks berita